2002
DOI: 10.1590/s0101-81752002000100004
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos reprodutivos de Sphoeroides greeleyi (Gilbert), Pisces, Osteichthyes, Tetraodontidae, da gamboa do Baguaçu, Baia De Paranaguá, Paraná, Brasil

Abstract: Reproductive aspects of Sphoeroides greeleyi (Gilbert), Tetraodontidae, from gam boa do Bagua~u, Paranagua, State of Parana, Brazil. The present study analyses the reproductive aspects of Sphoeroides greeleyi (Gilbert, 1900), such as morphology and hi stochemistry of carbohydrates in the oogenesis phases, maturity scale, time and type of spawn, sex ual rate and first ripened mature size for females. From the monthly captured animals (Nov 1998 to Nov 1999) the morphometric data (entire length and total weight) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 3 publications
1
11
0
2
Order By: Relevance
“…An explanation for this pattern is that the tide channel was dominated by the resident estuarine species A. parva, B. ronchus, G. genidens, S. greeleyi, and S. testudineus and the marine species H. clupeola, with similar life histories. The resident ones spawned at the site or close to the area in the spring and summer, and the marine species in the adjacent coastal zone (Chaves, 1989(Chaves, , 1995Rocha et al, 2002;Schultz et al, 2002), with the recruitment occurring mainly between the summer and beginning of winter. Reproduction in the spring and summer, with subsequent recruitment in the summer and autumn has been observed in most of the local species (Pinheiro, 1999;Chaves & Otto, 1999;.…”
Section: Eucinostomus Melanopterus Cynoscion Acoupa Cynoscion Leiarmentioning
confidence: 99%
“…An explanation for this pattern is that the tide channel was dominated by the resident estuarine species A. parva, B. ronchus, G. genidens, S. greeleyi, and S. testudineus and the marine species H. clupeola, with similar life histories. The resident ones spawned at the site or close to the area in the spring and summer, and the marine species in the adjacent coastal zone (Chaves, 1989(Chaves, , 1995Rocha et al, 2002;Schultz et al, 2002), with the recruitment occurring mainly between the summer and beginning of winter. Reproduction in the spring and summer, with subsequent recruitment in the summer and autumn has been observed in most of the local species (Pinheiro, 1999;Chaves & Otto, 1999;.…”
Section: Eucinostomus Melanopterus Cynoscion Acoupa Cynoscion Leiarmentioning
confidence: 99%
“…Algumas espécies estuarinas do referido local, tais como Sphoeroides greeleyi (Gilbert, 1900) (SCHULTZ et al 2002), Sphoeroides testudineus (Linnaeus, 1758) (ROCHA et al 2002) e Atherinella brasiliensis (Quoy & Gaimard, 1825) (FÁVARO et al 2003), já tiveram a sua reprodução analisada e assim, este trabalho fornece dados biológicos de mais uma espécie ecologicamente importante neste sistema.…”
unclassified
“…Juveniles were defined as those specimens presenting gonads at the immature stage (A), and adults, the specimens whose gonads were at the stages: maturation (B), mature (C), partially spawned (SD) or spawned/ spent (D). Histological characterization was based on the works of Schultz et al, 2002 andRocha et al, 2002, who studied the reproduction of these species in the same estuarine system.…”
Section: Discussionmentioning
confidence: 99%
“…Spach et al (2003) and Felix et al (2006) reported an increase in the catch rate of puffer fish during the period when temperatures are higher and, according to the community studies conducted by Godefroid et al (1997) and Santos et al (2002), there is an upward tendency in the abundance of fishes in the warmest periods of the year. Rocha et al (2002) and Schultz et al (2002), who studied the reproductive biology of S. greeleyi and S. testudineus in the estuarine complex of Paranaguá, established that the peak of reproductive activity for both species is in October (spring). The spawning season extends from October to February, while recruitment occurs over the subsequent months, corresponding to the summer and autumn.…”
Section: Temporal Variationmentioning
confidence: 99%
See 1 more Smart Citation